Kinetics and mechanism of vanadium catalysed asymmetric cyanohydrin synthesis in propylene carbonate - North, Michael; Omedes-Pujol, Marta (Beilstein Journal of Organic Chemistry, 2010)
Propylene carbonate can be used as a green solvent for the asymmetric synthesis of cyanohydrin trimethylsilyl ethers from aldehydes and trimethylsilyl cyanide catalysed by VO(salen)NCS, though reactions are slower in this solvent than the corresponding reactions carried out in dichloromethane. A mechanistic study has been undertaken, comparing the catalytic activity of VO(salen)NCS in propylene carbonate and dichloromethane. Reactions in both solvents obey overall second-order kinetics, the rate of reaction being dependent on the concentration of both the aldehyde and trimethylsilyl cyanide. The order with respect to VO(salen)NCS was determined and found to decrease from 1.2 in dichloromethane to 1.0 in propylene carbonate, indicating that in propylene carbonate, VO(salen)NCS is present only as a mononuclear species, whereas in dichloromethane dinuclear species are present which have previously been shown to be responsible for most of the catalytic activity. Evidence from 51V NMR spectroscopy suggested that propylene carbonate coordinates to VO(salen)NCS, blocking the free coordination site, thus inhibiting its Lewis acidity and accounting for the reduction in catalytic activity. This explanation was further supported by a Hammett analysis study, which indicated that Lewis base catalysis made a much greater contribution to the overall catalytic activity of VO(salen)NCS in propylene carbonate than in dichloromethane.
Keywords: cyanohydrin; Hammett; kinetics; propylene carbonate; vanadium

(untitled) - North, M.; Usanov, D. L.; Young, C. (Chem. Rev., 2008)

(untitled) - Brunel, J.-M.; Holmes, I. P. (Angew. Chem., Int. Ed., 2004)

(untitled) - Sharma, M.; Sharma, N. N.; Bhalla, T. C. (Enzyme Microb. Technol., 2005)

(untitled) - Purkarthofer, T.; Skranc, W.; Schuster, C.; Griengl, H. (Appl. Microbiol. Biotechnol., 2007)

(untitled) - Davie, E. A. C.; Mennen, S. M.; Xu, Y.; Miller, S. J. (Chem. Rev., 2007)

(untitled) - Denmark, S. E.; Beutner, G. L. (Angew. Chem., Int. Ed., 2008)

(untitled) - Schneider, C. (Angew. Chem., Int. Ed., 2009)

(untitled) - Shibasaki, M.; Kanai, M.; Matsunaga, S.; Kumagai, N. (Acc. Chem. Res., 2009)

(untitled) - Nájera, C.; Sansano, J. M.; Saá, J. M. (Eur. J. Org. Chem., 2009)

(untitled) - Breuer, M.; Ditrich, K.; Habicher, T.; Hauer, B.; Keßeler, M.; Stürmer, R.; Zelinski, T. (Angew. Chem., Int. Ed., 2004)

(untitled) - Belokon, Y. N.; Caveda-Cepas, S.; Green, B.; Ikonnikov, N. S.; Khrustalev, V. N.; Larichev, V. S.; Moscalenko, M. A.; North, M.; Orizu, C.; Tararov, V. I.; Tasinazzo, M.; Timofeeva, G. I.; et al. (J. Am. Chem. Soc., 1999)

(untitled) - Belokon, Y. N.; Gutnov, A. V.; Moskalenko, M. A.; Yashkina, L. V.; Lesovoy, D. E.; Ikonnikov, N. S.; Larichev, V. S.; North, M. (Chem. Commun., 2002)

(untitled) - Belokon, Y. N.; Carta, P.; Gutnov, A. V.; Maleev, V.; Moskalenko, M. A.; Yashkina, L. V.; Ikonnikov, N. S.; Voskoboev, N. V.; Khrustalev, V. N.; North, M. (Helv. Chim. Acta, 2002)

(untitled) - Belokon, Y. N.; Carta, P.; North, M. (Lett. Org. Chem., 2004)

(untitled) - Belokon, Y. N.; Blacker, A. J.; Carta, P.; Clutterbuck, L. A.; North, M. (Tetrahedron, 2004)

(untitled) - Belokon, Y. N.; Blacker, A. J.; Clutterbuck, L. A.; North, M. (Org. Lett., 2003)

(untitled) - Belokon, Y. N.; Ishibashi, E.; Nomura, H.; North, M. (Chem. Commun., 2006)

(untitled) - Lundgren, S.; Wingstrand, E.; Penhoat, M.; Moberg, C. (J. Am. Chem. Soc., 2005)

(untitled) - Wingstrand, E.; Lundgren, S.; Penhoat, M.; Moberg, C. (Pure Appl. Chem., 2006)

(untitled) - Belokon, Y. N.; Clegg, W.; Harrington, R. W.; Ishibashi, E.; Nomura, H.; North, M. (Tetrahedron, 2007)

(untitled) - Lundgren, S.; Wingstrand, E.; Moberg, C. (Adv. Synth. Catal., 2007)

(untitled) - Belokon, Y. N.; Green, B.; Ikonnikov, N. S.; North, M.; Tararov, V. I. (Tetrahedron Lett., 1999)

(untitled) - Belokon, Y. N.; Green, B.; Ikonnikov, N. S.; North, M.; Parsons, T.; Tararov, V. I. (Tetrahedron, 2001)

(untitled) - Zhang, Z.; Wang, Z.; Zhang, R.; Ding, K. (Angew. Chem., Int. Ed., 2010)

(untitled) - North, M. (Angew. Chem., Int. Ed., 2010)

(untitled) - Belokon, Y. N.; North, M.; Parsons, T. (Org. Lett., 2000)

(untitled) - Belokon, Y. N.; Maleev, V. I.; North, M.; Usanov, D. L. (Chem. Commun., 2006)

(untitled) - Belokon, Y. N.; Clegg, W.; Harrington, R. W.; Maleev, V. I.; North, M.; Omedes Pujol, M.; Usanov, D. L.; Young, C. (Chem.–Eur. J., 2009)

(untitled) - Blacker, A. J.; North, M.; Belokon, Y. N. (Chim. Oggi, 2004)

(untitled) - Baleizão, C.; Gigante, B.; Garcia, H.; Corma, A. (Green Chem., 2002)

(untitled) - Kim, G.-J.; Shin, J. H. (Catal. Lett., 1999)

(untitled) - Baleizão, C.; Gigante, B.; Garcia, H.; Corma, A. (J. Catal., 2003)

(untitled) - Baleizão, C.; Gigante, B.; Das, D.; Alvaro, M.; Garcia, H.; Corma, A. (Chem. Commun., 2003)

(untitled) - Baleizão, C.; Gigante, B.; Garcia, H.; Corma, A. (Tetrahedron Lett., 2003)

(untitled) - Baleizão, C.; Gigante, B.; Garcia, H.; Corma, A. (Tetrahedron, 2004)

(untitled) - Huang, W.; Song, Y.; Wang, J.; Cao, G.; Zheng, Z. (Tetrahedron, 2004)

(untitled) - Baleizão, C.; Gigante, B.; Garcia, H.; Corma, A. (J. Catal., 2004)

(untitled) - Baleizão, C.; Gigante, B.; Das, D.; Álvaro, M.; Garcia, H.; Corma, A. (J. Catal., 2004)

(untitled) - Kim, J. H.; Kim, G. J. (Catal. Lett., 2004)

(untitled) - Huang, W.; Song, Y.; Bai, C.; Cao, G.; Zheng, Z. (Tetrahedron Lett., 2004)

(untitled) - Khan, N. H.; Agrawal, S.; Kureshy, R. I.; Abdi, S. H. R.; Mayani, V. J.; Jasra, R. V. (Eur. J. Org. Chem., 2006)

(untitled) - Khan, N. H.; Agrawal, S.; Kureshy, R. I.; Abdi, S. H. R.; Mayani, V. J.; Jasra, R. V. (Tetrahedron: Asymmetry, 2006)

(untitled) - Lu, S.-F.; Herbert, B.; Haufe, G.; Laue, K. W.; Padgett, W. L.; Oshunlei, O.; Daly, J. W.; Kirk, K. L. (J. Med. Chem., 2000)

(untitled) - Dong, L.-C.; Crowe, M.; West, J.; Ammann, J. R. (Tetrahedron Lett., 2004)

(untitled) - Lloyd-Jones, G. C.; Wall, P. D.; Slaughter, J. L.; Parker, A. J.; Laffan, D. P. (Tetrahedron, 2006)

(untitled) - Belokon, Y. N.; Green, B.; Ikonnikov, N. S.; Larichev, V. S.; Lokshin, B. V.; Moscalenko, M. A.; North, M.; Orizu, C.; Peregudov, A. S.; Timofeeva, G. I. (Eur. J. Org. Chem., 2000)

(untitled) - Belokon, Y. N.; North, M.; Maleev, V. I.; Voskoboev, N. V.; Moskalenko, M. A.; Peregudov, A. S.; Dmitriev, A. V.; Ikonnikov, N. S.; Kagan, H. B. (Angew. Chem., Int. Ed., 2004)

(untitled) - Belokon, Y. N.; Clegg, W.; Harrington, R. W.; Young, C.; North, M. (Tetrahedron, 2007)

(untitled) - Chechik, V.; Conte, M.; Dransfield, T.; North, M.; Omedes-Pujol, M. (Chem. Commun., 2010)

(untitled) - Belokon’, Y. N.; Clegg, W.; Harrington, R. W.; North, M.; Young, C. (Inorg. Chem., 2008)

(untitled) - North, M.; Omedes-Pujol, M.; Williamson, C. (Chem.–Eur. J., 2010)

(untitled) - North, M.; Omedes-Pujol, M. (Tetrahedron Lett., 2009)

(untitled) - Reetz, M. T.; Lohmer, G. (Chem. Commun., 1996)

(untitled) - Behr, A.; Naendrup, F.; Obst, D. (Adv. Synth. Catal., 2002)

(untitled) - Behr, A.; Naendrup, F.; Obst, D. (Eur. J. Lipid Sci. Technol., 2002)

(untitled) - Bayardon, J.; Holz, J.; Schäffner, B.; Andrushko, V.; Verevkin, S.; Preetz, A.; Börner, A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Preetz, A.; Drexler, H.-J.; Fischer, C.; Dai, Z.; Börner, A.; Baumann, W.; Spannenberg, A.; Thede, R.; Heller, D. (Chem.–Eur. J., 2008)

(untitled) - Schäffner, B.; Holz, J.; Verevkin, S. P.; Börner, A. (Tetrahedron Lett., 2008)

(untitled) - Schäffner, B.; Andrushko, V.; Holz, J.; Verevkin, S. P.; Börner, A. (ChemSusChem, 2008)

(untitled) - Schnäffner, B.; Holz, J.; Verevkin, S. P.; Börner, A. (ChemSusChem, 2008)

(untitled) - North, M.; Pizzato, F.; Villuendas, P. (ChemSusChem, 2009)

(untitled) - Clegg, W.; Harrington, R. W.; North, M.; Pizzato, F.; Villuendas, P. (Tetrahedron: Asymmetry, 2010)

(untitled) - North, M.; Villuendas, P. (Org. Lett., 2010)

(untitled) - North, M.; Pasquale, R.; Young, C. (Green Chem., 2010)

(untitled) - Tullo, A. H.; Short, P. L. (Chem. Eng. News, 2006)

(untitled) - Meiers, R.; Dingerdissen, U.; Hölderich, W. F. (J. Catal., 1998)

(untitled) - Jenzer, G.; Mallat, T.; Maciejewski, M.; Eigenmann, F.; Baiker, A. (Appl. Catal., A, 2001)

(untitled) - Li, G.; Wang, X.; Yan, H.; Chen, Y.; Su, Q. (Appl. Catal., A, 2001)

(untitled) - Taylor, B.; Lauterbach, J.; Blau, G. E.; Delgass, W. N. (J. Catal., 2006)

(untitled) - Chen, Q.; Beckman, E. J. (Green Chem., 2007)

(untitled) - Chen, Q.; Beckman, E. J. (Green Chem., 2008)

(untitled) - Sheldon, R. A. (Chem. Commun., 2008)

(untitled) - Melendez, J.; North, M.; Pasquale, R. (Eur. J. Inorg. Chem., 2007)

(untitled) - North, M.; Pasquale, R. (Angew. Chem., Int. Ed., 2009)

(untitled) - Meléndez, J.; North, M.; Villuendas, P. (Chem. Commun., 2009)

(untitled) - Clegg, W.; Harrington, R. W.; North, M.; Pasquale, R. (Chem.–Eur. J., 2010)

(untitled) - North, M.; Villuendas, P.; Young, C. (Chem.–Eur. J., 2009)

(untitled) - Metcalfe, I. S.; North, M.; Pasquale, R.; Thursfield, A. (Energy Environ. Sci., 2010)

(untitled) - Norsikan, S.; Holmes, I.; Lagasse, F.; Kagan, H. B. (Tetrahedron Lett., 2002)

(untitled) - Silva, L. B.; Freitas, L. C. G. (THEOCHEM, 2007)

(untitled) - Chuit, C.; Corriu, R. J. P.; Reye, C.; Young, J. C. (Chem. Rev., 1993)

(untitled) - North, M.; Williamson, C. (Tetrahedron Lett., 2009)

(untitled) - North, M.; Villuendas, P.; Williamson, C. (Tetrahedron, 2010)

(untitled) - Sakai, T.; Wang, K.; Ema, T. (Tetrahedron, 2008)

(untitled) - Moon, L. S.; Jolly, R. S.; Kasetti, Y.; Bharatam, P. V. (Chem. Commun., 2009)